IMPLEMENTASI APLIKASI ARMADILLO ACCOUNTING UNTUK MENINGKATKAN KUALITAS PELAPORAN KEUANGAN PADA KOPERASI : (Studi Kasus Pada Koperasi Karyawan “Yodium Farma”) - Putri, Amadea Idhania Hartya; Magdalena , Marlina; Wahyuni, Hesti (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
The objective of this study was to actor the quality of financial reporting using the Armadillo Accounting Application which is used to record financial reports and daily transactions at the “Yodium Farma” Employee Cooperative. The study was carried out at the “Yodium Farma” Employee Cooperative. The research design was descriptive quantitative. The instruments of data collection were interviews and document study to obtain financial statement data obtained from the Armadillo Accounting Application in order to see the quality of financial reporting. The results of this study indicated that after using the Armadillo Accounting Application, recording the financial statements of the “Yodium Farma” Employee Cooperative has a good influence in recording financial reports and daily transactions. This improvement is measured using 10 financial reporting characteristics. The study revealed that the Armadillo Accounting Application provides good quality financial reporting at the “Yodium Farma” Employee Cooperative so that until now the application is still used for administrative activities.